An overview: Towards ontology-driven software development - Ahmad, Mohammad Nazir; Wahid, Mohd Taib (2006)
The Semantic Web and Software Engineering are two separate communities.Recent efforts in the context of Semantic Web vision have lead to a number of standards such as OWL and Web Services technologies.However, in the context of Software Engineering, most of software developers have little guidance on how to build a real-world Semantic Web application. In addition, most software developers are not aware of ontology concepts, which it is a backbone for the Semantic Web technologies. Therefore, recent research should be focused on creating a bridge between these two communities.This paper provides an overview on some backgrounds about ontology-driven software development particularly to review on recent efforts towards the development of real -world semantic web application. We outline a link between two separate communities by describing OMG’s efforts to bring MDA standard for ontology-driven software development. From the review, we agree that to give software developers a standard guidance on how to build real-world Semantic Web applications, the answer is OMG’s initiatives that lead to a standard in MDA- based where it can exploit current existing tools such as UML-based tool for developing ontology.Finally, we also try to point out some possible future works about the efforts.